Effect of high-intensity training in hypoxia on cycling performance and lactate metabolism - Ledcoultre, V.; Tappy, L.; Schneiter, Ph.; Schutz, Y. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Living and training at low altitude and adding some key training sessions in hypoxia (Live Low Train High (LLTH)) may be considered as an effective way of using altitude as a training stimulus for endurance athletes. It has also been shown to be effective in improving glucose tolerance in untrained individuals. However, its effects on performance are debated. Our hypothesis was that 4 weeks of LLTH would increase more endurance performance and lactate turnover rate of well trained cyclists than the same training regimen performed in normoxia. 14 cyclists participated to this study and replaced part of their weekly training schedule by 3 sessions performed in normobaric hypoxia (HYP) (~3000m) or normoxia (NOR) during 4 weeks. Before and after the training period, endurance performance was assessed during incremental tests performed in normoxia and hypoxia and a 40-km time-trial (TT) performed in normoxia. Lactate and glucose turnover rates were measured by means of stable isotope tracer infusion. After training TT performance was similarly and significantly improved in NOR and HYP. Maximal oxygen uptake was significantly (p<0.05) increased in NOR only. In hypoxia, a slight increase of maximal aerobic power and maximal ventilation (p<0.05) were measured in HYP. No effect of training was found on lactate turnover rates. In contrast, glucose metabolic clearance rate was decreased (p<0.05) and plasma concentration of insulin and glucose were increased after training in HYP (p<0.05). 3 athletes involved in HYP exhibited overtraining symptoms. Our results show no further effect of LLTH on sea-level endurance performance than does normoxic training and that LLTH may not improve performance at altitude. Thus questions are raised about the effectiveness of a LLTH protocol for performance enhancements and the athletes health with regard to the altered glucoregulation and overtraining.